Estimates of genetic variability, correlation and path analysis in Indian mustard (Brassica juncea L) - Bharat Chaudhary,; G Roopa Lavanya,; Ajay Pal Yadav,; Deepak Kumar Prajapati, (Journal of Oilseed Brassica, 2026)
Present investigation was undertaken to study the genetic variability, correlation and path analysis of twelve quantitativetraits in 20 Indian mustard (Brassica juncea) genotypes. The analysis of variance showed significant difference amonggenotypes for all the characters studied. High estimate of heritability coupled genetic advance as percentage of meanwas observed for seed yield per plant, 1000 seed weight, biological yield, siliqua per plant. High genotypic and phenotypiccoefficient of variation are studied for seed yield per plant, biological yield per plant, 1000 seed weight, harvest index.Seed yield per plant showed significant positive genotypic correlation with biological yield per plant, number of primarybranches and seeds per siliquae. Path coefficient at phenotypic and genotypic level reveled that have direct positiveeffect on seed yield per plant for that biological yield, primary branches, seeds per siliqua, days to 50 % flowering, siliquaper plant, harvest index, days to maturity.